Analisis Penerapan Standar Akuntansi Keuangan Entitas Tanpa Akuntanbilitas Publik (Sak Etap) pada Laporan Keuangan di Koperasi Karyawan Universitas Hang Tuah Surabaya Periode 2020-2023 - Virta Dwi Tri Agustina; Nur Ainiyah; Nurdiana Fitri Isnaini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Financial reports are an important tool for measuring the performance and financial health of cooperatives. Good financial reports are influenced by the level of knowledge and understanding of human resources in presenting financial reports. This research aims to find out how the financial reports in Kopkar UHT are and their application to SAK ETAP. The research was carried out using direct observation of research objects, interviews with specified informants, as well as documentation in the form of photos of activities and financial report documents. The findings show that Kopkar UHT's financial reports: presents the components of a balance sheet financial report, a report on the calculation of business results, a report on changes in capital, a recapitulation of income and expenses of USP and USW, a recapitulation of cash loans and bills, a recapitulation of turnover from sales of shop units, photocopy services and canteen services . Meanwhile, according to SAK ETAP, the presentation of financial statements consists of a Balance sheet, performance calculation report, capital changes report, cash flow report, CALK. This means that Kopkar UHT only displays three financial report components. that comply with SAK ETAP